Self-assessment of medical interns on the quality of emergency education at Babol University of Medical Sciences - Zahra Rostamtar; Sobhan rahimi; Mehdi Mohammadian Amiri; Hemmat Gholinia Ahangar; Maryam Ghaemi Amiri (Babol University of Medical Sciences, 2023)
Background and Objective: The emergency department in medical education, as one of the fundamental terms, plays a vital role. Assessing the quality of education in the emergency department in terms of clinical skills plays a key role in the improvement of educational systems in this field. The aim of this study is to determine the self-assessment of medical interns regarding the education in the emergency department. Methods: This study was conducted as a descriptive-cross-sectional study on 100 interns of Babol University of Medical Sciences. In this study, satisfaction with emergency department education in terms of "acquiring clinical skills in managing emergency patients","acquiring clinical skills in performing primary therapeutic interventions" and "quality of emergency department education" was examined. Finally, the collected data were analyzed using SPSS26 software. Findings: The average age of the participants was 25.54 ± 1.42 years. The results showed that in the field of emergency skills, the highest dissatisfaction of students was related to dealing with environmental emergencies, in the field of core skills, establishing airway management, and overall quality of emergency in creating motivation for study and research. Also, indices related to dealing with consciousness disorders, dealing with shortness of breath, and dealing with high blood pressure in the field of core skills were significantly correlated with age and/or gender. In the field of core skills, most of the indices were statistically correlated with age or gender. Conclusion: According to the findings, the need for planning and taking specific measures in the field of some clinical skills in the emergency department to increase the satisfaction of specified interns is emphasized.